Estimating the employment effects of recent minimum wage changes: Early evidence, an interpretative framework, and a pre-commitment to future analysis - Michael R. Strain; Jeffrey Clemens (American Enterprise Institute (AEI), 2017)
Clemens and Strain present early evidence on the employment effects of state minimum wage increases enacted between January 2013 and January 2015 and offer an interpretative framework to understand why it is of interest to study recent changes in isolation.
Keywords: A; 330; Minimum Wage